2018
DOI: 10.1038/s41433-018-0279-9
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of T cell pathogenesis in thyroid-associated ophthalmopathy

Abstract: Thyroid-associated ophthalmoapthy (TAO) is the most common orbital disease. As an autoimmune disorder, it is caused by self-reactive lymphocytes that escape immune tolerance, but the mechanism is not fully understood. The basic process of TAO is the infiltration of immune cells in orbital tissues, the activation of orbital fibroblasts (OFs), and the proliferation and differentiation of OFs and lymphocytes. Activated OFs secrete inflammatory regulators, growth factors, and chemokines, thereby maintaining and am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 70 publications
2
59
0
2
Order By: Relevance
“…What is more, it was observed that activated T cells release cytokines, such as tumor necrosis factor α (TNF-α), interleukin 1 β (IL-1β), interleukin 6 (IL-6), and interleukin (IL-17), which results in the increased production and recruitment of neutrophils and macrophages. This hypothesis partially explains neutrophilia, increased monocyte counts, and MLR values in the course of GD which were observed in our research [ 5 , 12 , 28 , 29 , 44 , 46 ].…”
Section: Discussionsupporting
confidence: 69%
“…What is more, it was observed that activated T cells release cytokines, such as tumor necrosis factor α (TNF-α), interleukin 1 β (IL-1β), interleukin 6 (IL-6), and interleukin (IL-17), which results in the increased production and recruitment of neutrophils and macrophages. This hypothesis partially explains neutrophilia, increased monocyte counts, and MLR values in the course of GD which were observed in our research [ 5 , 12 , 28 , 29 , 44 , 46 ].…”
Section: Discussionsupporting
confidence: 69%
“…Glucocorticoid therapy is a well-established treatment for TAO owing to its anti-inflammatory and immunosuppressive actions (9). Previous studies have focused on T lymphocytes, particularly CD4 + T-helper (Th) cells, which are the principal immune effector T cells (17,18). Activated CD4 + Th cells differentiate into Th1, Th2, Th17 and Treg subsets, which produce numerous cytokines (17).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on T lymphocytes, particularly CD4 + T-helper (Th) cells, which are the principal immune effector T cells (17,18). Activated CD4 + Th cells differentiate into Th1, Th2, Th17 and Treg subsets, which produce numerous cytokines (17). These cytokines have been proven to have an important role in TAO (3,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…T cell immunity plays an important role in the pathogenesis of GO ( 14 ). The frequency of Th1 cells and the Th1/Th2 ratio were positively correlated with the inflammatory activity score of GO ( 8 ).…”
Section: Discussionmentioning
confidence: 99%